The impact of conservation farming practices on Mediterranean agro-ecosystem services provisioning: a meta-analysis - Lee, Heera; Lautenbach, Sven; Cramer, Wolfgang (Regional environmental change, 2019)
In the Mediterranean region, the long-term provision of agro-ecosystem services is threatened by accelerating climate change, unsustainable farming practices, and other pressures. Alternative management practices such as conservation agriculture could be expected to ensure sustainability of ecosystem services from Mediterranean agro-ecosystems. Conservation agriculture is characterized by minimal soil disturbance, permanent soil cover, and diversification of crop species. We analyzed the impacts of several forms of alternative agricultural management practices (conservation tillage, cover cropping, mulching, manual weed management, organic fertilizer use, no-irrigation system) on multiple ecosystem services based on 155 published case studies (1994-2015). The effect size of various management options on four provisioning and four regulating ecosystem services were quantified. Impacts of conservation management options are not uniform. All regulating services were positively affected by the conservation management options except for the system without irrigation. In contrast, the provisioning services were inconsistently influenced by the conservation management options. For crop yield, environmentally sustainable soil management was beneficial, but organic fertilization (effect size = − 0.17), manual weed management (effect size = − 0.35), and no-irrigation system (effect size = − 0.5) led to lower crop yields. The impact on crop biomass was mainly negative but not significant. Water availability was especially important to enhance both provisioning and regulating services. Overall, alternative agriculture management practices led to more positive than negative effects on ecosystem services in the study region. Stimulating the application of conservation management practices is therefore an important policy option for decision-makers given the vulnerability of ecosystem services in the Mediterranean basin.